Team member exchange leadership model to improve company strategy development - Agung Edy Wibowo; Ida Bagus Udayana Putra; Ida Aju Brahma Ratih; Ida Bagus Cempena; Ida Aju Brahma Sari; Suhardi Suhardi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Company leaders have different potential and planning strategies. To develop a company requires leadership and team support. Many of the work teams do not experience positions alternately so that it affects the company's performance commitment. the research method uses library research by collecting several leadership theories and company The purpose of this study is to analyze the leadership model of the exchange of working team members to develop private companies in Indonesia. The results of the study explain that a company led by an entrepreneurial spirit, charismatic, democratic model is able to improve team performance so that the company can develop quickly through planning strategies and periodic evaluations from leaders and members of the work team. To thrive in the future and be profitable, teams and organizations can work alternately in a job title in a team member exchange leadership system.